2001
DOI: 10.1086/322262
|View full text |Cite
|
Sign up to set email alerts
|

Mid‐Infrared Spectral Energy Distribution of NGC 1068 with 0.̋1 Spatial Resolution

Abstract: The central region of the Seyfert 2 galaxy NGC 1068 is imaged in the mid infrared (MIR) using the Mid-Infrared Test Observation System on the 8.2 m Subaru Telescope. The oversampling pixel scale associated with shift-and-add method shows 0 ′′ .1 resolution images with a high dynamic range after deconvolution. Along with an extended structure at a position angle (P.A.) of −10 • with higher surface brightness, another structure extends wider with lower surface brightness at a P.A. of 20 • . The central peak elon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
73
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(83 citation statements)
references
References 34 publications
10
73
0
Order By: Relevance
“…As discussed by the authors, this coincidence between Hα and dust emission is comparable to what happens in galactic HII regions, and could be due to dust entrained into HII regions. Nevertheless, these features are clearly not detected in Mid-IR either by Bock et al (2000) or by Tomono et al (2001). An explanation could be the lower sensitivity of the 10 µm observations.…”
Section: Southern Structuresmentioning
confidence: 84%
“…As discussed by the authors, this coincidence between Hα and dust emission is comparable to what happens in galactic HII regions, and could be due to dust entrained into HII regions. Nevertheless, these features are clearly not detected in Mid-IR either by Bock et al (2000) or by Tomono et al (2001). An explanation could be the lower sensitivity of the 10 µm observations.…”
Section: Southern Structuresmentioning
confidence: 84%
“…At the highest spatial sampling, continuum core fluxes of 9-10 Jy have been reported around 12-μm (Mason et al 2006;Tomono et al 2001), and they correspond to log λL λ ≈ 43.8.…”
Section: A110 Ngc 6814mentioning
confidence: 96%
“…The original aims of this study were two-fold: (1) perform preliminary observations of active galaxies in order to prepare future observations with VISIR at the VLT, (2) look for extended MIR emission directly related to the AGN, as was observed along the radio jet direction in NGC 1068 (Alloin et al 2000;Bock et al 2000;Tomono et al 2001). To address these aims, we chose a sample of nearby (few Mpc) to moderately nearby (few hundreds of Mpc) AGN.…”
Section: Observationsmentioning
confidence: 99%
“…MIR imaging of this source at 0.6 resolution revealed extended and collimated 10 and 20 µm emission up to 5 from the core, along the direction of the radio jet (Alloin et al 2000). At higher angular resolution (0.1 after deconvolution: Bock et al 2000;Tomono et al 2001), the complex structure of the MIR emission is found to be coincident with the narrow line region (NLR) clouds (Galliano et al 2003). Therefore, the access to high resolution imaging brings new clues regarding the morphology of the material around the central engines of AGN.…”
Section: Introductionmentioning
confidence: 99%